2022
DOI: 10.1093/mnras/stac468
|View full text |Cite
|
Sign up to set email alerts
|

KaRMMa– kappa reconstruction for mass mapping

Abstract: We present KaRMMa, a novel method for performing mass map reconstruction from weak-lensing surveys. We employ a fully Bayesian approach with a physically motivated lognormal prior to sample from the posterior distribution of convergence maps. We test KaRMMa on a suite of dark matter N-body simulations with simulated DES Y1-like shear observations. We show that KaRMMa outperforms the basic Kaiser–Squires mass map reconstruction in two key ways: 1) our best map point estimate has lower residuals compared to Kais… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Figure 6 formalizes our visual impression, demonstrating that including the cross-correlations in the mass mapping procedure results in substantially improved cross-correlations between the sam-7 For a comparison to simulations and further discussion, see Fiedorowicz et al (2022). 8 A notable exception is the mass mapping method of Alsing et al (2016Alsing et al ( , 2017 pled maps and the true maps.…”
Section: Tomographic Mass Map Reconstructionmentioning
confidence: 56%
See 3 more Smart Citations
“…Figure 6 formalizes our visual impression, demonstrating that including the cross-correlations in the mass mapping procedure results in substantially improved cross-correlations between the sam-7 For a comparison to simulations and further discussion, see Fiedorowicz et al (2022). 8 A notable exception is the mass mapping method of Alsing et al (2016Alsing et al ( , 2017 pled maps and the true maps.…”
Section: Tomographic Mass Map Reconstructionmentioning
confidence: 56%
“…Our method reconstructs the mass maps assuming that the convergence field can be approximated as a multivariate lognormal distribution, thus recovering the correct one point and two point statistics, as well as peak and void counts, as measured in simulations (Fiedorowicz et al 2022). Our method also consistently accounts for cross correlations between different tomographic bins.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…More recently, Porqueres et al (2021) extended this work and demonstrated mass-map posterior sampling with a non-linear prior defined by a forward gravity model, but limited to very low angular resolution. Other Bayesian posterior sampling approaches include Schneider et al (2016) which relied on a Gaussian Process prior, which proposed a proximal MCMC approach to accommodate non-differentiable sparsity priors, and Fiedorowicz et al (2021) which relies on a log-normal prior.…”
Section: Introductionmentioning
confidence: 99%